Pengaruh Needs For Achievement Dan Karakteristik Pribadi Terhadap Keinginan Berwirausaha: Stud i Pada Mahasiswa FE Untar - Fanny Andriani Setiawan (Fakultas Ekonomi dan Bisnis, Universitas Tarumanagara, 2014)
The purpose of this study was to analyze Effect Needs for Achievement and Personal Characteristics Of Desire Entrepreneurship: Studies in FE Student UNTAR. The data used in this study is primary data obtained from a questionnaire research instruments were given to FE students UNTAR. Of the 500 questionnaires distributed, the number of questionnaires returned and deserves to dioleha of 420 questionnaires. Data using multiple regression analysis to answer the hypothesis peneilitian with the software PASW Statistics 18 and Eviews 6. This research was carried Faculty of Economics, University of Tarumanagara, with the object of study is a student. This study uses survey research with primary data collection using questionnaires. The selection of samples tested in this study using purposive sampling method, 420 respondents was selected as the study sample. The results of this study were (I) Needs for achievement has a positive effect on the willingness of students to entrepreneurship, (2) Gender positive effect on the willingness of students to entrepreneurship, (3) Age does not affect the desire of students to entrepreneurship, and (4) work experience possessed FE students UNTAR not affect students for entrepreneurship.